Pemanfaatan Media Sosial untuk Branding (Studi Deskriptif pada Vamelania Laundry) - Hendrico Y (Jurnal Sistem Informasi Dan Informatika, 2026)
Building branding on social media isn't just about posting great photos or diligently creating Stories. It's about how the audience perceives the Vamelania Laundry brand among millions of other content. Think of social media as a digital living room where you can chat with potential customers. Branding is the promise and feeling people remember when they hear a business name. Branding is creating a persuasive message that effectively attracts consumers' attention. Based on these facts, Instagram isn't just a place to show off photos in the world of branding; it's a Visual Showcase and Connection Center. Due to its highly visual nature, this platform plays a crucial role in shaping audience perceptions of a brand. Vamelania Laundry, a pioneer in machine-based laundry services, offered by the piece and by the kilo in 2007, promoted its services using Instagram. The purpose of this study was to determine the branding activities carried out by Vamelania Laundry on its Instagram social media account and to determine the factors that led to Instagram being chosen as an active branding medium. This research method used was descriptive qualitative, which is a fact-finding method by collecting data in the form of words and images, not numbers. Therefore, this study will contain several data excerpts to illustrate the presentation of the report. Researchers concluded that Vamelania Laundry utilizes Instagram effectively, as evidenced by its diverse branding activities and its ability to utilize various available features.